2021
DOI: 10.1038/s41398-021-01619-w
|View full text |Cite
|
Sign up to set email alerts
|

Altered resting-state functional connectome in major depressive disorder: a mega-analysis from the PsyMRI consortium

Abstract: Major depressive disorder (MDD) is associated with abnormal neural circuitry. It can be measured by assessing functional connectivity (FC) at resting-state functional MRI, that may help identifying neural markers of MDD and provide further efficient diagnosis and monitor treatment outcomes. The main aim of the present study is to investigate, in an unbiased way, functional alterations in patients with MDD using a large multi-center dataset from the PsyMRI consortium including 1546 participants from 19 centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 79 publications
5
49
0
1
Order By: Relevance
“…The SMN closely coordinates with other ICNs and has been implicated in several functions associated with error detection, motor planning and initiation, motor inhibition, the subjective urge to move, experience of bodily awareness and pain, and the fine-tuning of cognitive and executive functions ( 260 264 ). Neuroimaging studies have indicated that nodes of the SMN display reduced activity ( 265 , 266 ) and within-network connectivity ( 86 , 88 , 158 , 267 , 268 ) in MDD patients, which has been further supported by a recent mega-analysis ( 269 ). Sensorimotor interventions, such as music, light, tone, and physical exercise, are also well-known to modulate depressive symptoms ( 270 ).…”
Section: Intrinsic Connectivity Network Biomarkers Of Ketamine Antide...mentioning
confidence: 77%
See 1 more Smart Citation
“…The SMN closely coordinates with other ICNs and has been implicated in several functions associated with error detection, motor planning and initiation, motor inhibition, the subjective urge to move, experience of bodily awareness and pain, and the fine-tuning of cognitive and executive functions ( 260 264 ). Neuroimaging studies have indicated that nodes of the SMN display reduced activity ( 265 , 266 ) and within-network connectivity ( 86 , 88 , 158 , 267 , 268 ) in MDD patients, which has been further supported by a recent mega-analysis ( 269 ). Sensorimotor interventions, such as music, light, tone, and physical exercise, are also well-known to modulate depressive symptoms ( 270 ).…”
Section: Intrinsic Connectivity Network Biomarkers Of Ketamine Antide...mentioning
confidence: 77%
“…Impaired top-down control is thought to be attributed to diminished CEN connectivity, which has been seen in depressed individuals at rest ( 64 , 78 80 ) and during tasks involving working memory ( 81 ), executive control ( 82 ), and affective interference ( 83 ). Hypoconnectivity within the SMN has been linked with the symptoms of psychomotor retardation ( 84 , 85 ), and several studies have shown this association among patients with MDD ( 30 , 86 88 ). A relatively “new” ICN incorporated into the network model is the CAN, which involves the HPT, AMYG, insula, and brainstem nuclei responsible for the control of bodily autonomic responses ( 61 , 89 ).…”
Section: Introduction To Intrinsic Connectivity Network In Major Depr...mentioning
confidence: 99%
“…More specifically, hyperconnectivity within the DMN and hypoactivity within the CEN have frequently been observed in reviews and meta‐analyses. Contradictory, a recent mega‐analysis did not find decreases within the CEN and DMN, whereas another reported DMN hypoactivation 21,22 …”
Section: Findings and Developmentsmentioning
confidence: 93%
“…Contradictory, a recent megaanalysis did not find decreases within the CEN and DMN, whereas another reported DMN hypoactivation. 21,22 rs-fMRI has also been studied to identify biomarkers of treatment outcome. Increased FC within areas of the DMN such as the posterior cingulate cortex and medial prefrontal cortex (mPFC) and decreased FC within areas of the cognitive control network such as the insula, ACC, and dlPFC have shown to separate antidepressant treatment-resistant from treatment-responsive MDD patients.…”
Section: Findings and Developmentsmentioning
confidence: 99%
“…For example, a prior restingstate fMRI study has documented aberrant connectivity of the FPN with the SN and DMN leads to imbalance of externally attention process and internally self-reference and furthermore gives rise to emotional dysregulation (21). Another study based on meta-analysis reported hyperconnectivity between the SN and DMN is associated with overreaction to negative stimuli, which results in distorted information processing (22). Reduced connectivity between the executive network (EN) and DMN contributes to higher cognitive dysfunction (23).…”
Section: Introductionmentioning
confidence: 99%